Efektivitas Media Audio Visual pada Mata Pelajaran Pendidikan Agama Islam terhadap Hasil Belajar Siswa di SMP Negeri 4 Banjarbaru: Meningkatkan Hasil Belajar Siswa dalam Pendidikan Islam melalui Penggunaan Media Audio-Visual (Studi Eksperimental di SMP Negeri 4 Banjarbaru) - Yahya, Dadang Syaiful; Rachmah, Imaniah Elfa (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2025)
This study examines the effect of using audio-visual media in Islamic Religious Education on student learning outcomes at SMP Negeri 4 Banjarbaru. The focus of the study includes the significance of the effectiveness of audio-visual media on student learning outcomes and the extent to which the media is effective in improving students' understanding of Islamic Religious Education. This research is a field study with a quantitative descriptive approach, using a quasi-experimental method through a non-equivalent pretest-posttest design. The design involved one experimental class and one control class, each consisting of 31 students, for a total sample of 62 students selected through purposive sampling from a population of 911 students. Data were obtained through questionnaires, tests, and documentation, then analyzed using quantitative descriptive analysis techniques, including validity, reliability, difficulty level, discrimination power, distractor effectiveness, and normality tests. In addition, n-gain calculations were used to assess learning outcome improvement. The research findings show that the use of audio-visual media has a significant effect on improving student learning outcomes. Based on the analysis results, the effectiveness of audio-visual media is in the